Broiler Management - The First 24 Hours - Gary D. Butcher; Amir H. Nilipour (EDIS, 2003)
More than 30 billion broiler chicks are produced worldwide on an annual basis. Fifteen billion of these are produced in the Americas. Due to the poultry industry's tendency towards more intensive production practices and increased automation, the tender loving care once afforded to chickens in grow-out has been replaced with a mass production mentality. As a result, newly hatched chicks are often subjected to numerous stressors in the first 24 hours after hatching. These adverse effects during the critical early hours following hatch can result in an increased percentage of early mortality. These early stressors also influence final performance, resulting in declines in final body weights, increases in feed conversions and cost per pound of meat produced. Farm personal must understand that they have become the "adoptive parents" of these chicks. Without attention to details, successful and profitable grow-out is not realized. This document is VM124, one of a series of the Veterinary Medicine-Large Animal Clinical Sciences Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Original publication date May 1, 2002.